2019
DOI: 10.3389/fpsyg.2019.01835
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality in Educational Inclusion. A Systematic Review on the Last Decade

Abstract: The use of Augmented Reality (AR) to achieve educational inclusion has been not deeply explored. This systematic review describes the current state of using AR as an educational technology that takes into consideration the needs of all students including those with a disability. It is done through the analysis of factors, such as the advantages of AR, its limitations, uses, challenges, its scope in the educational field, the attended population and the positive or negative effects of its use in learning scenar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(93 citation statements)
references
References 69 publications
3
79
0
11
Order By: Relevance
“…Este resultado torna en consonancia de los resultados expresados en investigaciones previas (Cabero & Roig, 2019;Tzima, Styliaras & Bassounas, 2019). De esta misma manera, la inferencia extraída de este estudio también guarda relación con los resultados de las revisiones sistemáticas referenciadas anteriormente, lo cual aporta consistencia al argumento que pretende dar este trabajo (Pellas, Fotaris, Kazanidis & Wells, 2019;Quintero, Baldiris, Rubira, Cerón & Vélez, 2019).…”
Section: Discusión Y Conclusionesunclassified
“…Este resultado torna en consonancia de los resultados expresados en investigaciones previas (Cabero & Roig, 2019;Tzima, Styliaras & Bassounas, 2019). De esta misma manera, la inferencia extraída de este estudio también guarda relación con los resultados de las revisiones sistemáticas referenciadas anteriormente, lo cual aporta consistencia al argumento que pretende dar este trabajo (Pellas, Fotaris, Kazanidis & Wells, 2019;Quintero, Baldiris, Rubira, Cerón & Vélez, 2019).…”
Section: Discusión Y Conclusionesunclassified
“…AR is a variant of virtual reality (VR), adding, deleting, emphasizing, or attenuating information in the surrounding reality at the time in question, literally expanding the real world seen by humans [14,15]. While VR replaces reality with an artificially constructed reality, AR modifies part of reality [14,15]. Information has been presented for all human sense organs and somatosensory sensations, including sight, hearing, and touch, as a way to extend the reality of computers.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, augmented reality (AR) is a new technology that provides new awareness by using a computer to extend the real environment perceived by humans, that is, by superimposing information on objects in the reality space [14,15]. AR was introduced in the medical field in recent years, and there are reports of its use for diagnostic imaging and surgical support [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…10 In a systematic review of AR in educational inclusion in the last decade, the main advantages reported in the studies included increasing motivation, facilitating interaction, and maintaining the interest of students. 11 In our own review, we have previously concluded that is a valuable tool, because ASD children's interest is aroused by this technology, which they find attractive and motivating. 12,13 AR applications can stimulate problem-solving skills for cognitive empowerment in typically or atypically developing children, as well as promoting inclusion and social integration as would be desirable in educational and group rehabilitation settings.…”
Section: Introductionmentioning
confidence: 99%